Analysis of associations between risk factors for cardiovascular disease and breast cancer - Ruijie NIU; Jun ZENG; Zhoutong LI; Cheng WANG; Jinquan JIANG (Zhongguo Linchuang Yixue)
ObjectiveTo explore the associations between risk factors for cardiovascular disease and breast cancer. MethodsA total of 300 patients with breast cancer and 300 with benign breast diseases diagnosed by postoperative pathology were included in the Department of Breast Surgery, Huangpu Branch of the Ninth People’s Hospital, Shanghai Jiao Tong University School of Medicine from January 2023 to June 2023. The main cardiovascular risk factors in patients between the two groups were compared. Stratification was performed according to menstrual status, and the main cardiovascular risk factors in patients with different menstrual status between the two groups were compared. The logistic regression correlation analysis was used to analyze the risk factors related to cardiovascular disease for breast cancer. ResultsThere were statistically significant differences in clinical data and laboratory indicators between the two groups (P＜0.01) . Multivariate logistic regression analysis showed that age (OR=1.03, P=0.029), triglyceride (TG; OR=1.94, P=0.025), C-reactive protein (CRP; OR=2.73, P＜0.001), D-dimer (OR=61.19, P＜0.001), and homocysteine (Hcy; OR=2.10, P＜0.001) were independently associated with breast cancer. The stratified analysis showed age, TG, CRP, D-dimer, and Hcy were independently associated with breast cancer in both premenopausal and postmenopausal patients (P＜0.05). ConclusionsAmong risk factors for cardiovascular disease, advanced age, increased TG, CRP, D-dimer, and Hcy might increase breast cancer risk, which are helpful of screening high-risk individuals for breast cancer.